2002
DOI: 10.1007/s11886-002-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve sclerosis as a marker of active atherosclerosis

Abstract: Aortic sclerosis is a calcific disease of the aortic valvular leaflets defined as focal leaflet thickening without significant obstruction to left ventricular outflow. Several clinical factors are associated with calcific aortic valve disease, including male sex, smoking, hypertension, age, hypercholesterolemia, and diabetes. Histologic and biochemical studies suggest similarities between the mechanisms involved in the development of aortic sclerosis and atherosclerosis, suggesting these two diseases may share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
5
20
0
2
Order By: Relevance
“…In one study, Matsuoka and colleagues [30] reported a lower 5-year cumulative survival (67.9%) for haemodialysis patients with CAC scores above the median for Although strong associations were present between calcification of both valves and CAC !1000, this association was stronger for the aortic valve. Interestingly, this observation matches the purported similarity of aortic valve disease and atherosclerosis described in the general population, and supports the notion that calcification of vessels and valves follows similar mechanisms even in the context of end-stage renal disease [31,32]. On the contrary, no pattern was present between pulse pressure and CAC.…”
Section: Discussionsupporting
confidence: 87%
“…In one study, Matsuoka and colleagues [30] reported a lower 5-year cumulative survival (67.9%) for haemodialysis patients with CAC scores above the median for Although strong associations were present between calcification of both valves and CAC !1000, this association was stronger for the aortic valve. Interestingly, this observation matches the purported similarity of aortic valve disease and atherosclerosis described in the general population, and supports the notion that calcification of vessels and valves follows similar mechanisms even in the context of end-stage renal disease [31,32]. On the contrary, no pattern was present between pulse pressure and CAC.…”
Section: Discussionsupporting
confidence: 87%
“…First of all, the high prevalence of older subjects with AS in our study population and the frequent association of valve stenosis with coronary and extra-coronary (carotid and peripheral) atherosclerotic diseases confirm the recent hypothesis that calcific AS is a presentation of atherosclerosis, with process of valve fibrosis and calcification resembling the different phases of arterial plaque formation and progression [25,26]. The presence of atherosclerotic risk factors, such as high blood pressure, hypercholesterolemia and diabetes, in over 80%, 60% and 30%, respectively, of our AS pts, might confirm the similarity of pathogenetic processes leading to atherosclerotic disease and calcific AS [26].…”
Section: Discussionsupporting
confidence: 84%
“…However, the data on the increased activity of MMP-2 and MMP-9 in human valve stenosis (Jian et al 2001;Kaden et al 2004) agree well with the enhanced activity of MMPs in the sera and the aorta of H animals obtained in our study. Since no difference has been detected in the gene expression of MMPs in the aorta and aortic valves of patients with aortic stenosis (Wilton et al 2008), and given that aortic valve sclerosis is currently seen as a marker of systemic atherosclerosis (Branch et al 2002), we consider that our results are comparable with those obtained for aortic stenosis. No reports have been presented on the effect of clodronate-encapsulated liposomes on MMPs activities in aortic stenosis.…”
Section: Discussionsupporting
confidence: 71%